Associations between social networks, messaging apps, addictive behaviors, and sleep problems in adolescents: the EHDLA study - María Navalón-González; José Adrián Montenegro-Espinosa; Héctor Gutiérrez-Espinoza; Jorge Olivares-Arancibia; Rodrigo Yañéz-Sepúlveda; Daniel Duclos-Bastías; Daniel Duclos-Bastías; Miriam Garrido-Miguel; Miriam Garrido-Miguel; Miriam Garrido-Miguel; Arthur Eumann Mesas; José Francisco López-Gil; et al. (Frontiers in Behavioral Neuroscience)
ObjectiveThe current study aims to provide a comprehensive analysis of the relationships between social network (SN) use, messaging apps use, and addictive behaviors related to SNs, and sleep-related problems in a sample of Spanish adolescents.MethodsThis was a cross-sectional study using data from the Eating Healthy and Daily Life Activities (EHDLA) project, which involved adolescents aged 12–17 years from three secondary schools in Valle de Ricote (Region of Murcia, Spain). A sample of 632 adolescents was studied. The use of SN (i.e., Facebook, Twitter, Instagram, Snapchat or TikTok) or messaging applications (i.e., WhatsApp) was assessed via a scale including one item for each SN, in which adolescents were asked what type of SN they used and the usage profile of each SN. The Short Social Networks Addiction Scale-6 Symptoms (SNAddS-6S) was used to determine SN addictive behaviors. Generalized linear regression analyses with a negative binomial distribution were performed to determine the associations of SN use or SN addictive behaviors with sleep-related problems. These analyses were adjusted for age, sex, body mass index, socioeconomic level, physical activity, sedentary behavior, and adherence to the Mediterranean diet.ResultsHigher SN use was related to greater presence of sleep-related problems [prevalence ratio (PR) = 1.04; 95% confidence interval (CI) 1.01–1.07; p = 0.015]. Additionally, the higher the score on the addictive behaviors toward SN use scale was, the more sleep-related problems were identified (PR = 1.15; 95% Cl 1.09 to 1.21; p < 0.001). Specifically, only the use of Twitter was significantly associated with sleep-related problems (PR = 1.10; 95% Cl 1.01 to 1.21; p = 0.035). In terms of addictive behaviors related to SN use, mood modification, relapse, withdrawal, and conflict were significantly associated with sleep-related problems (mood modification: PR = 1.58; 95% CI 1.36 to 1.84; p < 0.001; relapse: PR = 1.24; 95% CI 1.07 to 1.43; p = 0.004; withdrawal: PR = 1.28; 95% CI 1.08 to 1.51; p = 0.004; conflict: PR = 1.19; 95% CI 1.01 to 1.39; p = 0.037).ConclusionOur results suggest a relationship between SN use, SN addictive behaviors, and sleep-related problems in adolescents. These cross-sectional results should be confirmed in longitudinal and intervention studies.